Considerations on the cost analysis of Pediatric Intensive Care Units in Italy. - D. Galante (Pediatric Anesthesia and Critical Care Journal (PACCJ))
The healthcare system in Italy is known for its universal coverage and high-quality medical services, with pediat- ric intensive care units (PICUs) being a crucial compo- nent in the care of critically ill children. As medical tech- nologies advance and the number of children requiring intensive care continues to grow, understanding the costs associated with providing these services becomes in- creasingly important. This article examines the cost anal- ysis of pediatric intensive care units (PICUs) in Italy, ad- dressing factors influencing healthcare expenditure, the efficiency of PICU management, and the economic im- plications for the national health system.